Makna Kerinduan dalam Syair Risālah min Taḥt al-Mā’ Karya Nizar Qabbani: Tinjauan Semantik - Rizqi Haidir; Ekawati Ekawati; Mutiara Dila; Prameswari Dwi Auliya Humaerah; Muhammad Daffa ‘Izzul Islam Amanulloh; Badriyatun Nashifah (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2026)
This study aims to analyze the denotative and connotative meanings found in the poem Risālah min Taḥt al-Mā’ by Nizar Qabbani. This research employs a descriptive, qualitative method, using Ahmad Mukhtar Umar’s semantic theory, to examine each stanza of the poem and reveal the meanings embedded in it. The primary data of this research is the poem itself, while the secondary data consist of relevant journals, books, and other supporting sources. The findings of this study reveal that the meaning of longing in the poem Risālah min Taḥt al-Mā’ emerges through a semantic analysis of the words and symbols employed by Nizar Qabbani. Through the mapping of denotative and connotative meanings, it was found that longing is not merely presented as physical distance of absence, but as an inner condition that torments, engulfs, and obstructs the poet’s communication with the beloved. The semantic analysis table indicates that each chosen diction contains layers of meaning that reinforce the portrayal of longing as an emotional experience. Thus, this study demonstrates that the semantic approach is effective in identifying and explaining the construction of longing embedded within Qabbani’s poetic language, thereby fulfilling the research objective as stated in the title.